NORMA SUBYEKTIF DAN SELF-EFFICACY DALAM PENERIMAAN APLIKASI REKSA DANA DAN SAHAM - Primastiwi, Anita; Adi Kurniawan, Taufan; Andriany, Devina (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
Mutual funds and shares are investment elements that are more volatile compared to gold, but in the long term they are quite profitable elements. This can be seen during the COVID-19 pandemic, the Russian-Ukrainian war crisis, and the bankruptcy of a large bank in America, this investment element still provides profits. The financial technology industry also provides various service applications on mobile phones or smartphones that make it easier for people to invest in mutual funds and shares. This research analyzes the determinants of Indonesian society's acceptance of stock mutual fund applications using the Technology Acceptance Model (TAM) and adding two external variables, namely subjective norms and self-efficacy. This research uses Structural Equation Model-Partial Least Square (SEM-PLS) to test the hypothesis. The results show that all TAM variables and subjective norms have an influence, but self-efficacy does not influence interest in using mutual fund and stock applications. In order to increase public acceptance of mutual fund and stock investment applications, and then interest in using them, service providers should improve the ease of operation and usefulness of their applications. Efforts should also be made to encourage people to recommend each other to invest through this application.